Understanding The Influence Of Corporate Social Responsibility and Brand Image on Customer Loyalty, Using Customer Satisfaction as an Intermediary Factor - Indriawati, Alfira Agustina (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
Purpose: This research aims to examine the influence of corporate social responsibility (CSR) and brand image on customer loyalty, with customer satisfaction as a mediating variable. Methodology: A quantitative method with a survey approach was applied, using data collected through questionnaires distributed to relevant customers. Data were analyzed using Structural Equation Modeling (SEM) to test the relationships among the variables. Results: The findings reveal that CSR and brand image significantly affect customer satisfaction, which in turn enhances customer loyalty. Findings: Customer satisfaction plays a critical mediating role, linking the direct effects of CSR and brand image to customer loyalty. Originality: This research develops an integrative model that combines CSR, brand image, and customer satisfaction, offering a comprehensive perspective on their relationships. Novelty: The study highlights the mediating role of customer satisfaction, providing novel insights into how CSR and brand image contribute to loyalty. Conclusions: Companies should prioritize CSR initiatives and maintain a strong brand image to foster customer satisfaction and loyalty sustainably.Type of Paper: Empirical research paper.